(untitled) (Atti del Sodalizio Glottologico Milanese, 2014)
The article discusses some Latin and Sabellic personal names showing /Op-/ and /Ops-/ in the first syllable and attempts to establish the appurtenance of these types to one (or, in some cases, more than one) lexical item(s) and their morphological structure as well as, eventually, their meanings. The dossier of names with /Op-/ and /Ops-/ appears to be very heterogeneous and lets recognize a possible etymological link to at least four lexical items, all of them of Indo-European origin and well represented in the Italic area. KEYWORDS: Latin, Sabellic, anthroponyms, Italic languages, etymology